EXPLORING EFL LEARNERS’ GRAMMATICAL ERROR IN PARAGRAPH WRITING - Aditya Rizaldi; Dian Anik Cahyani (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2020)
Writing is the most difficult skill in English, so most English as a foreign language (EFL) learners tend to make errors in writing. In assisting the learners to sucessfully acquire writing skill, the analysis of errors and the understanding of their sources are neccessary. This study attempts to explore the types of grammatical errors occurred in the paragraph writing of EFL learners based on the linguistics taxonomy. It also investigates the most grammatical error that presents in their writing. Twenty-eight of paragraph writing composed by EFL learners were collected and analysed.  Result showed that there were six types of grammatical error found in EFL learners’ worksheet of paragraph writing and indefinite article incorrect an used for a was found to be the dominant of errors.